THE USE OF THE SCHOOL LIBRARY AT THE ELEMENTARY SCHOOL SD NEGERI 2 PEJAGOAN - Safitri, Nurul; Widiyani, Tri Purna; Hanifah, Umi; Hidayah, Ratna (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Libraries are important facilities in schools. One of the schools that has a library is SD Negeri 2 Pejagoan. Obsviously school libraries are used by students and teachers to support learning. But not all school libraries are well untilized. The purpose of this study was to describe the use of school libraries in SD Negeri 2 Pejagoan. The method used in this study is a qualitative descriptive method with data retrieval techniques, interviews, and observations. Extracting data involves there components, they are students, to teachers, and librarians. The results of this study are that the school library in the SD Negeri 2 Pejagoan has been used well. Research indicators are based on the size of the library collection, attendance intensity, and service. The percentages of the library collection 83.2% have been well benefited, while a percentage of attendance at 66.1 percent each day, and 93% of the visitors have been greatly assisted by the service provided by the library. Implementation of this study is to get the school to use the library at maximum.